The Influence of Principals and Teachers on Improving Mathematics Achievement of Elementary School Students Using Google Classroom - Suwondo Suwondo; Sri Marmuah; Budi Usodo (STAI Hubbulwathan Duri, 2022)
At this time there is a shift in the learning system from face-to-face learning to a challenge. One of the bold lessons used is google classroom. There are still many principals who managerially have not maximized the learning of teachers and students in the process with this google classroom media, besides that teachers who should be the spearhead of implementing learning through google classroom also have not mastered this media to the fullest. So learning with google classroom media still has many obstacles. This study aims to measure the extent of the influence of principal managerial and teacher performance on the use of google classroom in improving mathematics learning achievement in elementary school students. This research method uses descriptive qualitative with a phenomenological approach. The subjects of this study were principals, teachers, and school students in Kepyar Village. The data collection used in this research is data collection through questionnaires, interviews, observations, and documentation. Data validity through triangulation of data sources. The results of this study are the managerial influence and performance of teachers who use google classroom to improve students' mathematics learning achievement in elementary schools. The benefit of this research is to provide a reference to teachers that the managerial influence of principals and effective teacher performance in the use of google classroom can improve student achievement in mathematics lessons in elementary school.